Bibliometric and visualized analysis of 2014–2024 publications on therapy for diabetic peripheral neuropathy - Fu, Baitian; Luo, Ning; Zeng, Yichen; Chen, Yutian; Wie, Low Je; Fang, Jianqiao (Frontiers in Neuroscience, 2024)
BackgroundThis research aimed to examine the global developing patterns in the treatment of diabetic peripheral neuropathy (DPN) using a bibliometric analysis of published literature.MethodsWe extracted publication data from papers published between 2014 and 2024 using a specific topic search in the “Web of Science Core Collection” (WoSCC) database. Various metrics, such as the number of papers, citations, authors, countries, institutions, and references, were collected for analysis. To further explore the data, CiteSpace was employed to examine co-citation patterns among authors, identify collaborative efforts between countries and institutions, and uncover emerging trends using burst keywords and reference analysis.ResultsThe study encompassed 2,488 publications that exhibited an increasing trend in annual output. Notably, the journal PAIN, the United States, the Pfizer institution, and the author Feldman, EvaL emerged as the most prolific contributors to this research domain. The term “placebo-controlled trial” was the most prominent burst keyword from 2014 to 2017, whereas “spinal cord stimulation” held this distinction in the recent 5-year span. Furthermore, the publication titled “Pharmacotherapy for neuropathic pain in adults: a systematic review and meta-analysis-2015” demonstrated the highest burst in terms of references.ConclusionThis study is the first to objectively reveal the current hotspots and trends in DPN treatment. The results indicate that drug therapy remains the primary first-line treatment for DPN and that future research on DPN treatment will likely focus on “spinal cord stimulation” and “pain management.” These findings provide valuable insights into DPN treatment.